Degradation of buried ice and permafrost in the Veleta cirque (Sierra Nevada, Spain) from 2006 to 2013 as a response to recent climate trends - Gómez-Ortiz, A. (2014)
The Veleta cirque is located at the foot of the Veleta peak, one of the highest summits of the Sierra Nevada National Park (southern Spain). This cirque was the source of a glacier valley during the Quaternary cold periods. During the Little Ice Age it sheltered a small glacier, the most southerly in Europe, about which we have possessed written records since the 17th century. This glacier still had ice residues until the mid-20th century. This ice is no longer visible, but a residue persists along with discontinuous permafrost trapped under strata of rock blocks that make up an incipient rock glacier. From 2006 to 2013, this rock glacier was monitored by measurement of the temperature of the active layer, the degree of snow cover on the ground, movements of the body of the rock glacier and geophysical prospection inside it. The results show that the relict ice and trapped permafrost have been steadily declining. The processes that explain this degradation occur in chain, starting from the external radiation that affects the ground in summer, which is when the temperatures are higher. In effect, when this radiation steadily melts the snow on the ground, the thermal expansive wave advances into the heart of the active layer, reaching the ceiling of the frozen mass, which it then degrades and melts. In this entire linked process, the circulation of meltwaters ful-fils a highly significant function, as they act as heat transmitters. The complementary nature of these processes explains the subsidence and continuous changes in the entire clastic pack and the melting of the frozen ceiling on which it rests. This happens in summer in just a few weeks. All these events, in particular the geomorphological ones, take place on the Sierra Nevada peaks within certain climate conditions that are at present unfavourable to the maintenance of snow on the ground in summer. These conditions could be related to recent variations in the climate, starting in the mid-19th century and most markedly since the second half of the 20th century. The work and results highlight the climate sensitivity of the peaks of the Sierra Nevada to the effect of climate change and its impact on the dynamics of ecosystems, which is a benchmark for evaluating the current evolution of landscapes of Mediterranean high mountains.